2001
DOI: 10.1051/0004-6361:20000045
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of photoionization and star formation in starbursts and H1214 II galaxies

Abstract: Abstract. We analyze coherently the stellar and nebular energy distributions of starbursts and H ii galaxies, using our evolutionary synthesis model, PÉGASE (Fioc & Rocca-Volmerange 1997, 2000, coupled to the photoionization code CLOUDY (Ferland 1996). The originality of this study is to relate the evolution and the metallicity of the starburst to the past star formation history of the host galaxy. Extinction and geometrical effects on emission lines and continua are computed in coherency with metallicity. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 64 publications
(110 reference statements)
3
62
0
Order By: Relevance
“…In this respect our approach is similar to that of Pérez-González et al (2003a,b) who also use observed line ratios for their sample of strong H α emitting UCM survey galaxies. It differs from those of Charlot & Longhetti (2001), Moy et al (2001), or Zackrisson et al (2001, who assume electron densities and temperatures for the gas at low metallicities and couple a photoionisation code to their evolutionary synthesis model.…”
Section: Gaseous Emissionmentioning
confidence: 99%
“…In this respect our approach is similar to that of Pérez-González et al (2003a,b) who also use observed line ratios for their sample of strong H α emitting UCM survey galaxies. It differs from those of Charlot & Longhetti (2001), Moy et al (2001), or Zackrisson et al (2001, who assume electron densities and temperatures for the gas at low metallicities and couple a photoionisation code to their evolutionary synthesis model.…”
Section: Gaseous Emissionmentioning
confidence: 99%
“…[Nii]/Hα diagrams. This choice has been made by considering that these emission line ratios do not depend strongly on the age of the stellar population (Moy et al 2001;Stasińska & Izotov 2003;Stasińska et al 2006). (Figs.…”
Section: Comparison With Modelsmentioning
confidence: 99%
“…Other hydrogen and metals lines are then rescaled in fixed proportions. Moy et al (2001) have improved the previous model by coupling the integrated spectrum with CLOUDY.…”
Section: Nebular Emission From a Star-forming Galaxymentioning
confidence: 99%